2022
DOI: 10.2147/idr.s377465
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Predictive Biomarkers for Type 2 Diabetes Mellitus in Active Pulmonary Tuberculosis Patients

Abstract: Purpose This study was to explore the predictive value of monocyte to high-density lipoprotein cholesterol ratio (MHR), neutrophils to high-density lipoprotein cholesterol ratio (NHR), C-reactive protein-to-lymphocyte ratio (CLR), and C-reactive protein-to-albumin ratio (CAR) for type 2 diabetes mellitus (T2DM) in patients with active pulmonary tuberculosis (APTB). Patients and Methods A total of 991 active pulmonary tuberculosis (APTB) patients (201 with T2DM) were hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…CAR is a better marker for inflammation and nutritional status than CRP or albumin alone. Qi et al found that CAR is a useful marker to predict diabetes mellitus in patients with pulmonary tuberculosis [ 25 ]. Interestingly, there have been no studies that investigated the correlation between CAR and RP-ILD, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAR is a better marker for inflammation and nutritional status than CRP or albumin alone. Qi et al found that CAR is a useful marker to predict diabetes mellitus in patients with pulmonary tuberculosis [ 25 ]. Interestingly, there have been no studies that investigated the correlation between CAR and RP-ILD, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The red blood cell distribution width (RDW), a simple index in peripheral blood circulation, reflects the size heterogeneity of red blood cells, commonly used for differential diagnosis of anemia [ 26 ]. Several studies have demonstrated that elevated RDW is correlated with inflammatory status in various diseases [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, high-sensitivity C-reactive protein to lymphocyte ratio (HSCLR) was proven to be an important biomarker for distinguishing active PTB from inactive PTB ( Yu et al., 2022b ). Similarly, CLR can be used to predict the prevalence of T2DM in patients with active PTB ( Yu et al., 2022a ). To our best knowledge, the current study is the first to explore the correlation between CPR and prognosis of TB.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that there is an increase in monocytes, neutrophils and a decrease in serum lymphocytes in type 2 DM patients with active pulmonary TB infection [5]. Studies also show that pulmonary TB infection in people with type 2 diabetes can affect immune system disorders, especially the cellular components, namely Neutrophil Lymphocyte Ratio (NLR) and Monocyte Lymphocyte Ratio (MLR) which are used as markers of pulmonary TB infection (Yu et al, 2022) [6].…”
Section: Internationalmentioning
confidence: 99%
“…Lacerda (2017) also said that the inflammatory response in TB suppresses leptin production directly through loss of body fat mass and decreased energy intake, decreased leptin leads to decreased cellular immunity [36].. According to Yu et al, (2022) leptin is a proinflammatory hormone found to be significantly increased in DM and TB patients [6].…”
Section: Active Pulmonary Tb P-value Pr (95%ci) Yesmentioning
confidence: 99%